Geology and depositional environment of Gua Musang formation in the Perasu area, Gua Musang Kelantan - Nor Intan Shazlin Mohamad Rojali (2019)
The large scale of geological map (1: 750 000) does not give sufficient information about each outcrop in the study area. In addition, there is no previous study explain about depositional environment of Gua Musang Formation in the study area. Thus geology and depositional environment of Gua Musang Formation in the Felda Perasu area was determined. To achieve the objective, different materials and equipment such as hammer, compass and gps was used to collect and record sample. From geological mapping and analysis, the study area show few structures such as fold, quartz vein and joint. From field and petrography analysis, the lithologies that consist in the study area is limestone, siliclastic, volcaniclastic, extrusive volcanic and metasediments. Besides that, also prepare lithology to study depositional environment of study area. Three parameters were used to determined depositional environment which is lithology, sedimentary structure and fossils. Based on all the evidence elaborates, the depositional environment of the Gua Musang Formation in the study area at the shallow marine carbonate setting. This study produces geological map which is useful for detail observation and give significantly to industrial, construction and economic activity.